Zootechnical and physiological performance of broilers in the final stage of growth subjected to different levels of heat stress (2018)
The objective of this work was to study the influence of different levels of thermal stress from the environment, including comfort levels (25 °C), heat stress (28 °C), moderate heat(31 °C), high heat (34 °C) and severe heat (37 °C), on the performance of broilers in the late growth (22-42 days), housed in environmental chambers. It has been determined the physiological and behavioral parameters of chickens (weight gain (WG), day weight gain (DWG), feed intake (FI), feed conversion ratio (FC), mortality (MORT), percentage of carcass of age as body weight (BW), carcass (CAR), breast (Bre), drumstick (Drum), wings (Win)), according the specific ranges of temperature; and was calculated the Temperature Index Black Globe Humidity (BGHI), for control and evaluation of the thermal environment of the treatments. In general, birds kept in temperature between 25-28 °C, during the three last week of life, performed better than those exposed to other situations, and indicating this would be the ambient temperature to the desired setting for birds in its final phase, compared with the other treatments, including those who remained at recommended temperature as thermal comfort throughout the experimental period.